استقلالية البنك المركزي في ظل التمويل الغير تقليدي - حدة, طواهرية; مريم, العيفاوي; تركية, بولعراس (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى تسليط الضوء على موضوع استقلالية البنك المركزي في ظل التمويل غير التقليدي ، دراسة حالة بنك الجزائر. حيث تطرقنا إلى مفاهيم الدراسة ألا وهي البنك المركزي، واستقلالية البنك المركزي والتمويل غير التقليدي ،حيث قمنا بتقييم استقلالية البنك المركزي في ظل التمويل غير التقليدي باستخدام مؤشر كوكيرمان. ولمعالجة إشكالية الدراسة والتوصل إلى النتائج المرغوبة قمنا باستخدام الأسلوب التحليلي اعتمادا على بعض الجداول التي ساعدتنا في قياس درجة الاستقلالية. وقد توصلت الدراسة في الأخير إلى أن استقلالية البنك المركزي لم تصل إلى الحد المطلوب عكس ما شهدنه الدول الأخرى، رغم صدور قانون النقد والقرض والامر03/11 الذي ساهم في دعم الاستقلالية. ""This study aims to shed light on the issue of the independence of the central bank in light of unconventional financing, a case study of the Bank of Algeria. Where we dealt with the concepts of the study, namely the central bank, the independence of the central bank and unconventional financing, where we assessed the independence of the central bank in light of unconventional financing using the Cocke²rman index. To address the problem of the study and reach the desired results, we used the analytical method based on some tables that helped us in measuring the degree of independence. Finally, the study concluded that the independence of the Central Bank did not reach the required level, unlike what other countries have witnessed, despite the issuance of the Currency and Credit Law and the decree 11/03 that contributed to supporting independence. "
مذكرة ماستر اقتصاد نقدي وبنكي
Keywords: بنك الجزائر، استقلالية البنك المركزي ، التمويل غير التقليدي، قانون النقد والقرض، مؤشر كوكيرمان.; Bank of Algeria, Central Bank Independence, Unconventional Finance, Currency and Credit Law, Cockerman Index.